Integrate the question below
![Integrate the question below class=](https://us-static.z-dn.net/files/d92/a889338770cca2e01af95e7a8496b97d.jpg)
It looks like the integral is
[tex]\displaystyle \int_0^1 \frac{2x - 8x^2}{1+4x} \, dx[/tex]
Polynomial division yields
[tex]\dfrac{2x-8x^2}{1+4x} = -2x + 1 - \dfrac1{1+4x}[/tex]
Now split up the integral as
[tex]\displaystyle \int_0^1 \left(-2x + 1 - \frac1{1+4x}\right) \, dx = \int_0^1 (1-2x) \, dx - \int_0^1 \frac{dx}{1+4x}[/tex]
In the second integral, substitute [tex]u=1+4x[/tex] and [tex]du=4\,dx[/tex]. Then [tex]x=0 \implies u=1[/tex] and [tex]x=1 \implies u=5[/tex], so
[tex]\displaystyle \int_0^1 \frac{dx}{1+4x} = \frac14 \int_1^5 \frac{du}u[/tex]
and by the fundamental theorem of calculus, the integral we want evaluates to
[tex]\displaystyle \int_0^1 \left(-2x + 1 - \frac1{1+4x}\right) \, dx = \int_0^1 (1-2x) \, dx - \frac14 \int_1^5 \frac{du}u \\\\ = (x - x^2)\bigg|_{x=0}^{x=1} - \frac14 \ln|u| \bigg|_{u=1}^{u=5} \\\\ = \bigg((1 - 1^2) - (0 - 0^2)\bigg) - \frac14 (\ln(5) - \ln(1)) = \boxed{-\frac{\ln(5)}4}[/tex]